2005
DOI: 10.1021/la047878e
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Boundary Lubricant Film Modified by an Amphiphilic Diblock Copolymer

Abstract: The effect of the uptake of a low-molecular-weight amphiphilic diblock copolymer on the morphology of didodecyldimethylammonium bromide (DDAB) adsorbed layers on mica, the interactions between two coated surfaces, and the frictional properties of the boundary film have been studied using an atomic force microscope and a dynamic surface forces apparatus nanotribometer. When DDAB-coated surfaces in aqueous solution were compressed, hemifusion or removal of the adsorbed surfactant bilayers could not be induced, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…In SFA experiments it has been demonstrated that this surfactant bilayer has sufficient cohesion to withstand shear under high loads, and the friction force was found to be so small that it could not be measured with the very accurate and sensitive SFA tribometer. 48 Phospholipids are naturally occurring bilayer-forming amphiphiles. They are readily deposited on solid surfaces, and their headgroups are strongly hydrated.…”
Section: Amphiphilic Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…In SFA experiments it has been demonstrated that this surfactant bilayer has sufficient cohesion to withstand shear under high loads, and the friction force was found to be so small that it could not be measured with the very accurate and sensitive SFA tribometer. 48 Phospholipids are naturally occurring bilayer-forming amphiphiles. They are readily deposited on solid surfaces, and their headgroups are strongly hydrated.…”
Section: Amphiphilic Moleculesmentioning
confidence: 99%
“…Drummond and co-workers have explored this in some detail, using surfactants that adsorb onto the substrate surface mixed with a diblock copolymer to modify the lubrication performance. 44,48,79,80 In their initial studies, using a double-chained surfactant which in itself provided low friction and high load bearing capacity, it was found that coadsorption of a hydrophobically end-modified poly(ethylene oxide) compromised the lubrication performance. 48 In later studies oligomeric cationic surfactants were utilized, and the layers formed by these surfactants alone had relatively low load bearing capacity.…”
Section: Load Bearing Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Niedostateczne właściwości smarne płuczki mogą z kolei prowadzić do szeregu problemów, takich jak zwiększone zużycie łożysk świdra, zużywanie kolumn rur okładzinowych, wzrost momentu obrotowego czy przyklejanie przewodu wiertniczego [1,3,11]. To właśnie niska smarność płuczki wiertniczej uważana jest za jeden z ważniejszych, po zbyt dużej różni-cy pomiędzy ciśnieniem hydrostatycznym a ciśnieniem formacji, powodów przyklejania się przewodu wiertniczego do osadu filtracyjnego pokrywającego ścianę otworu.…”
Section: Wstępunclassified
“…Investigations on friction properties of silica, glass or mica in presence of silane and surfactant mixture are not available in the literature. A few studies only concern mixtures containing a cationic surfactant mixed with a copolymer 9 , an anionic surfactant 10 or an alcohol 11 . In this work, we focus on the surfactant lubricant effect in the context of competing silane adsorption for a 3 better understanding on the mechanisms involved in the protecting effect of the sizing.…”
Section: Introductionmentioning
confidence: 99%